Warm-up procedures to enhance dynamic muscular performance - Naokazu Miyamoto (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Warm-up routine prior to sports activities is a customary practice among sporting people and athletes. Although warm-up is done with the expectation that it will enhance subsequent performance, little is known about how one should warm-up. In addition, scientific evidence is lacking on the best procedure that would allow for optimal preparation for a given event, especially for explosive sports activities such as jumping and sprinting. Recently, there has been considerable research on the functional significance of activity-dependent potentiation in dynamic muscular performance. Interest has evolved around whether high-intensity, short-duration muscle contraction as a warm-up procedure can improve such performance, although it remains inconclusive since muscle contractions induce fatigue as well as potentiative effects. In this review, based on evidence from well-controlled studies, proper warm-up procedures for enhancing voluntary dynamic muscular performance are proposed from the perspective of both fatigue and potentiative effects.